1995
DOI: 10.1111/j.1365-2222.1995.tb00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B4 production by blood neutrophils in allergic rhinitis—effects of cetirizine

Abstract: As LTB4 is an important chemotactic factor, Cetirizine could act on inflammatory cell recruitment by inhibiting LTB4 production by neutrophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…These in vitro data were confirmed in several in vivo conditions in atopic subjects. It was shown for instance that the drug inhibited the release of LTC 4 and LTB 4 from leukocytes of patients treated with the drug [20, 21]. Moreover Naclerio [22]showed that oral administration of CTZ significantly inhibits the appearance of LTC 4 in the nasal lavage fluid after antigen provocation in atopics, and finally Michel et al [23]showed that the drug inhibits the rise in histamine skin of atopics during an antigen–induced late–phase reaction (skin chamber technique).…”
Section: The Inhibition Of Mediator Releasementioning
confidence: 99%
“…These in vitro data were confirmed in several in vivo conditions in atopic subjects. It was shown for instance that the drug inhibited the release of LTC 4 and LTB 4 from leukocytes of patients treated with the drug [20, 21]. Moreover Naclerio [22]showed that oral administration of CTZ significantly inhibits the appearance of LTC 4 in the nasal lavage fluid after antigen provocation in atopics, and finally Michel et al [23]showed that the drug inhibits the rise in histamine skin of atopics during an antigen–induced late–phase reaction (skin chamber technique).…”
Section: The Inhibition Of Mediator Releasementioning
confidence: 99%
“…Antiinflammatory activity of cetirizine has been documented in a variety of in vitro as well as in vivo animal and human studies. It inhibits eosinophil accumulation at skin, conjunctiva, reduces LTB 4 , and LTC 4 production from blood leucocytes [75][76][77]. Cetirizine has been shown to be able to reduce nasal inflammatory infiltration and cytokine production in children with PAR [78].…”
Section: Cetirizinementioning
confidence: 97%
“…CET could act on inflammatory cell recruitment by inhibiting LTB 4 production by PMNL [335]. The administration of CET does not alter human PMNL chemotaxis and O 2 .-production [189].…”
Section: Ah and Pmnls In Clinical Practicementioning
confidence: 99%